Skid resistance and the effect of temperature - Shafii, Mohd Amin (2009)
Skid resistance is the force developed when a tire that is prevented from rotating slides along the pavement surface. It is the most important characteristic of the road pavement. In the wet conditions, skidding will occur easily when the water film covering the pavement act as lubricant and reduce the friction between the tire and pavement. There are several factors that influence skid resistance such as road pavement texture, aggregate characteristic and surface temperature. Although a number of researcher have attempted to explain and quantify the effect of temperature on pavement skid resistance properties, the result are still unclear. Therefore, the objective of this study is to investigate the effect of pavement surface temperature on the pavement skid resistance properties of different type of mixtures. Besides, this study also wants to investigate whether the type of gradation has a significant effect on skid resistance based on temperature difference. To accomplish the objectives of the study, five types of mixture consist of ACW 14, ACW 10, Porous Mix Grade A, Porous Mix Grade B and SMA 14 were prepared. Then, the skid resistance test using British Pendulum Tester was conducted. The test was conducted using heated temperature method and natural temperature method. The results of skid resistance using heated temperature method were compared with the result of skid resistance using natural temperature method. In this study, it is found that temperature has a significant effect on skid resistance value and the relationship between skid resistance value and temperature can be represent using quadratic curve. Based on temperature different, type of gradation also has significant effect to the skid resistance value.